Interstitial pneumonia with autoimmune features in a patient with melanoma differentiation-associated gene 5 (MDA5) antibody. Issue 11 (30th November 2020) - Hong, Lih En; Proudman, Susanna; Limaye, Vidya
Abstract : Melanoma differentiation-associated gene 5 (MDA5) antibody, also known as anti-CADM140 antibody is recognised to be associated with rapidly progressive interstitial lung disease, which can be fatal within 3 months. It is also known to be associated with amyopathic dermatomyositis. We report a case of MDA5 antibody-associated interstitial pneumonia with autoimmune features, without cutaneous features of dermatomyositis, in a Sudanese patient with dual positive antibodies to Ro52. The patient notably had several features associated with poor prognosis, including age, high serum ferritin level, anti-Ro52 antibodies and progressive lung infiltrates during treatment.